KOMPOSISI TIPE NEMATOSIT KARANG SCLERACTINIA, Pocillopora sp. DARI TERUMBU KARANG PANTAI TONTAYUO, BATUDAA PANTAI, GORONTALO - Ajrin Y Nusi; Carolus Paulus Paruntu; Antonius P Rumengan; Farnis B Boneka; Noldy G F Mamangkey; Laurentius Th X Lalamentik (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The objective of this present study is to know the composition of nematocyst types from the coral Scleractinia, Pocillopora sp. The coral colonies of Pocillopora sp. were collected at Tontayuo coastal coral reefs, Batudaa Pantai, Gorontalo. This research was conducted for 3 months, from September-December 2020. The method of testing the type and composition of nematocysts was carried out using an Olympus CX41 type microscope with x100 objective lens magnification connected to a computer ST24 monitor equipped with optical view 7 application (software). Photos of Pocillopora sp. both alive and skeleton form are documented in this journal. The results of the current study showed that Pocillopora sp. has the types and composition of MpM of 91.49%, while HI is 8.51%. MpM is the dominant nematocyst in Pocillopora sp. Future research is recommended to identify this coral at the species level and to study more deeply the various coral species in the genus Pocillopora based on the types and morphology of nematocysts that are useful in the taxonomy of Scleractinia corals.Keywords: Gorontalo, HI, MpM, nematocyst, Pocillopora sp., Scleractinian coral